BUSINESS DEVELOPMENT STRATEGY ANALYSIS ON HEROS TEA BUSINESS - Armanto, Achmad Alfredo; Wibowo, Januar; Fianto, Achmad Yanu Alif; Candraningrat, Candraningrat (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
In this Covid-19 pandemic situation, many business actors sell various kinds of health products such as masks, health supplements, as well as food and drinks that contain many benefits for the body. Seeing this business opportunity, a business emerged, namely Heros Tea. Heros Tea is a business that produces processed herbal plants into tea drinks, for example, rosella flower tea. Rosella flowers contain many benefits and properties for the body, which are rich in antioxidants, and can lower blood pressure, and can lower cholesterol levels. This study uses the Business Model Canvas and SWOT analysis method which is used to anticipate the problems that exist in the Heros Tea business, namely the lack of manpower, high raw material prices, and not having a business development plan for the future. Besides being used to anticipate problems, this method is used to develop the Heros Tea business in surviving the competition with existing competitors. The results of this business research show that the Heros Tea business is at the quadrant I level, which means that the Heros Tea business is in an aggressive strategy and has a favorable situation in developing the business.